Licensing of Pilots in the Autistic Spectrum – A Comparative Study - Abeyratne, Ruwantissa (Frontiers in Law, 2026)
The licensing of pilots diagnosed with autism spectrum disorder (ASD) reveals a pervasive regulatory ambiguity across the United States, Europe, Canada, and the international framework established by ICAO. None of these jurisdictions has produced authoritative jurisprudence or explicit statutory guidance that directly addresses autism in the context of aeromedical certification, thereby leaving a vacuum in both legal doctrine and administrative practice. In the United States, the body of case law concerning mental-health assessments and medication use offers analogies but no direct engagement with ASD, while Europe’s policy projects—such as MESAFE—advance conceptual reforms without generating judicial precedent. Canada’s functional “medical fitness” standard permits discretionary assessment yet remains untested in autism-specific litigation. ICAO, for its part, provides only general mental-health criteria within Annex 1, declining to enumerate autism or any neurodevelopmental condition, thereby reinforcing the primacy of national discretion. The cumulative effect is a regulatory silence that leaves the treatment of autistic pilots to case-by-case clinical judgment rather than harmonized norms. This absence of clarity underscores the tension between safety-driven precaution and the equitable recognition of neurodiverse individuals, and it signals an urgent need for more transparent, evidence-based, and consistent frameworks in global aviation medicine.